Application of partial grounding technique for ultra wide band antenna - Moniruzzaman, Mohd; Muhammad, Ghulam; Ul Haque, Asrar; Islam, Md Rafiqul; Zaidi, Saleem H (American-Eurasian Network for Scientific Information (AENSI), 2012)
Application of partial grounding technique to improve the fractional band width (FBW) of microstrip antennas for ultra wide band (UWB) applications is investigated in this work. Several antennas are designed with variable width of partial ground to observe the impact of partial ground on antenna performance. Each of the antennas has a step and a microstrip feed. Industry standard EM simulator Ansoft HFSS is used to evaluate the performance of the antennas. The best FBW was obtained as 100.05%. All of the antennas showed more than 20% FBW, which is the minimum requirement for UWB applications. The antennas are designed on a low cost, small sized substrate to be suitable for compact portable and handheld applications.